2022
DOI: 10.1002/cam4.4557
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of primary neuroendocrine breast cancer: A population‐based study

Abstract: Background Primary neuroendocrine breast carcinomas (NEBCs) are an extremely rare and underrecognized subtype of mammalian carcinoma. The prognostic factors for NEBCs remain controversial. Methods In this multicenter retrospective study, the prognostic factors for patients with primary NEBCs who underwent surgery and had a pathologically confirmed diagnosis of neuroendocrine carcinoma in China and the United States were examined. The endpoints were disease‐free survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Br-NEN rarely affects males, in our cohort we had no male patient. Age and family history are currently considered the primary risk factors for Br-NEN, similar to non-neuroendocrine BC (8,9,18,19). In the largest study with over 140 Chinese and American patients with neuroendocrine breast carcinomas the tumor grade and Ki-67 levels played a crucial role as prognostic factors for disease-free survival (DFS), while the age and ER status were significant prognostic factors for overall survival (OS) (9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Br-NEN rarely affects males, in our cohort we had no male patient. Age and family history are currently considered the primary risk factors for Br-NEN, similar to non-neuroendocrine BC (8,9,18,19). In the largest study with over 140 Chinese and American patients with neuroendocrine breast carcinomas the tumor grade and Ki-67 levels played a crucial role as prognostic factors for disease-free survival (DFS), while the age and ER status were significant prognostic factors for overall survival (OS) (9).…”
Section: Resultsmentioning
confidence: 99%
“…Due to their diverse nature and rarity, prognostic factors as well as treatment guidelines remain controversial. Br-NENs are usually luminal (ER and/or PR) positive and HER-2 negative (7,9). Data regarding prognosis are ambiguous, and it appears that few factors can influence it, including the level of expression of neuroendocrine markers, grade, stage, Ki-67 level, and presence of ER/PR (8).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have confirmed that NEC has a higher rate of local recurrence, a higher rate of lymph node metastasis, and worse survival than IDC 14,15 . Considering that clinical variables such as age at initial diagnosis, molecular subtype and tumour stage may be potential confounders in survival analysis, coupled with the fact that pathological grade and Ki‐67 are prognostic factors for NEC, 6 our team obtained a similar conclusion after eliminating differences in clinical characteristics between IDC and NEC cohorts by propensity score matching that NEC had worse DFS than IDC. Therefore, we believe that the type of breast neuroendocrine neoplasms should be clarified during survival analysis to give readers a clearer elucidation.…”
Section: Discussionmentioning
confidence: 99%
“…All information was collected from a routine medical records system using a self‐designed case report form (CRF). Additional details are provided in another study by our team 6 …”
Section: Methodsmentioning
confidence: 99%
“…Evidence shows that the NEBC grade and Ki67 percentage are prognostic factors affecting disease-free survival and that age and ER status are prognostic factors impacting overall survival. 5 …”
Section: Introductionmentioning
confidence: 99%